(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this paper is to study and compare the biological characteristics of natural and commercial probiotic. The probiotics that were studied were Lactic Acid Bacteria. They were isolated from cow milk and Bifilac. The information obtained from this study could contribute to the potential use of these lactobacilli isolates in the food and pharmaceutical industries.